The integrated high-resolution reflection-mode photoacoustic and fluorescence confocal microscopy - Chengbo Liu; Jiuling Liao; Longchao Chen; Jianhua Chen; Rubo Ding; Xiaojing Gong; Caimei Cui; Zhiqiang Pang; Wei Zheng; Liang Song (Photoacoustics, 2019)
A dual modality microscopy with the highest imaging resolution reported so far based on reflection-mode photoacoustic and confocal fluorescence is presented in this study. The unique design of the imaging head of the microscope makes it highly convenient for scalable high-resolution imaging by simply switching the optical objectives. The submicron resolution performance of the system is demonstrated via in vivo imaging of zebrafish, normal mouse ear, and a xenograft tumor model inoculated in the mouse ear. The imaging results confirm that the presented dual-modality microscopy imaging system could play a vital role in observing model organism, studying tumor angiogenesis and assessment of antineoplastic drugs. MSC: 00-01, 99-00, Keywords: Photoacoustic microscopy, Confocal microscopy, Multimodal imaging